Design and prototyping of the planar inverted-F antenna for V2X communications - Berrich, Loubna; Addaim, Adnane (Institute of Advanced Engineering and Science, 2026)
In the context of intelligent transportation systems (ITS) development, vehicle-to-everything (V2X) communication plays a central role by enabling information exchange between vehicles (V2V), infrastructure (V2I), pedestrians (V2P), and the network (V2N). The effectiveness of these systems relies heavily on the performance of the antennas employed, which must meet strict requirements in terms of compactness, bandwidth, gain, and electromagnetic compatibility. One of the main challenges lies in designing antennas suitable for the embedded vehicular environment, where space is limited and the propagation conditions are complex. In this context, the present study aims to design, simulate, fabricate, and experimentally evaluate a planar inverted-F antenna (PIFA) dedicated to V2X communication in the 5.8 GHz band. The primary objective is to develop an antenna that is both compact and high-performing, tailored to the specific constraints of V2X applications. The adopted methodology involves a comprehensive parametric study, focusing on several key design parameters that influence the antenna’s performance, such as substrate selection, feeding point location, and the addition of a slot in the structure. These factors are analyzed to optimize the radiation characteristics, resonant frequency, and impedance matching of the antenna. The results demonstrate the feasibility of a PIFA antenna that offers an excellent trade-off between miniaturization and performance, making it well suited for V2X communication applications at 5.8 GHz.